Prevalence of Atrial Fibrillation and Antithrombotic Therapy in Hemodialysis Patients: Cross-Sectional Results of the Vienna InVestigation of AtriaL Fibrillation and Thromboembolism in Patients on HemoDIalysis (VIVALDI). - Oliver Königsbrügge; Florian Posch; Marlies Antlanger; Josef Kovarik; Renate Klauser-Braun; Josef Kletzmayr; Sabine Schmaldienst; Martin Auinger; Günther Zuntner; Matthias Lorenz; Ella Grilz; Gerald Stampfel; et al. (PLoS ONE, 2017)
Background Atrial fibrillation (AF) adds significant risk of stroke and thromboembolism in patients on hemodialysis (HD). The aim of this study was to investigate the prevalence of AF in a population-based cohort of HD patients and practice patterns of antithrombotic therapy for stroke prevention in AF. Methods The Vienna InVestigation of AtriaL fibrillation and thromboembolism in patients on hemodialysis (VIVALDI), an ongoing prospective observational cohort study, investigates the prevalence of AF and the risk of thromboembolic events in HD patients in Vienna, Austria. We analyzed cross-sectional data of 626 patients (63.4% men, median age 66 years, approx. 73% of HD patients in Vienna), who provided informed consent. A structured interview with each patient was performed, recent and archived ECGs were viewed and medical histories were verified with electronic records. Results The overall prevalence of AF was 26.5% (166 patients, 71.1% men, median age 72 years) of which 57.8% had paroxysmal AF, 3.0% persistent AF, 32.5% permanent AF, and 6.6% of patients had newly diagnosed AF. The median CHA2DS2-VASc Score was 4 [25th-75th percentile 3-5]. In multivariable analysis, AF was independently associated with age (odds ratio: 1.05 per year increase, 95% confidence interval: 1.03-1.07), male sex (1.7, 1.1-2.6), history of venous thromboembolism (2.0, 1.1-3.6), congestive heart failure (1.7, 1.1-2.5), history of or active cancer (1.5, 1.0-2.4) and time on HD (1.08 per year on HD, 1.03-1.13). Antithrombotic treatment was applied in 84.4% of AF patients (anticoagulant agents in 29.5%, antiplatelet agents in 33.7%, and both in 21.1%). In AF patients, vitamin-K-antagonists were used more often than low-molecular-weight heparins (30.1% and 19.9%). Conclusions The prevalence of AF is high amongst HD patients and is associated with age, sex, and distinct comorbidities. Practice patterns of antithrombotic treatment indicate a lack of consensus for stroke prevention in HD patients with AF.